Improving multiplication counting skills of class IV students using PBL model and Jarimatica technique - Amelia Citra; Sisriawan Laapasere; Asriani; Pahriadi; Surahman (Jurnal Elementaria Edukasia, 2024)
This research is quantitative in nature using a non-equivalent control group design. The sample consisted of class IVA as the controlling classes and the IVB as the experiment classes. The instrument used is an essay test that has been validated both validity and reliability. The analysis data was carried out with prerequisite test including tests for normality and homogeneity, as well as testing of hypotheses using the paired sample t-test, with help the IBM SPSS Statistics 25. The results show that a significance the value (2-tailed) of 0.000 less than the alpha value of 0.05. Since 0.000 less than 0.05, the alternative hypothesis (Ha) is accept and the null hypothesis (Ho) is reject. Therefore, conclusion is that the problem-based learning model and the finger math technique significantly improve the counting multiplication skills of SD Inpres 7 Labuan Baru fourth graders. Keywords: Problem Based Learning Model; Jarimatica Technique; Multiplication Counting Ability